2009
DOI: 10.1021/ja806565t
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Kinetic Enhancement in Hydrogen Absorption and Desorption of the Li−Mg−N−H System

Abstract: High operating temperature and slow kinetics retard the practical applications of the Li-Mg-N-H system for hydrogen storage. To alleviate these problems, a first attempt was carried out by synthesizing Li(2)MgN(2)H(2) through sintering a mixture of Mg(NH(2))(2)-2LiNH(2) and investigating its size-dependent hydrogen storage performance. A dramatically enhanced kinetics for hydrogen absorption/desorption was achieved with a reduction in the particle size. For the dehydrogenation reaction, a three-dimensional dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 38 publications
4
144
0
1
Order By: Relevance
“…The broad peak seen in the lower angle region is attributed to the kapton film used to prevent oxidation of the samples during measurement. The pattern of the Spex milled sample did reveal peak broadening and lower intensity indicating a decrease in particle size and an increase in defects [29]. Using the Scherrer equation to determine particle size from XRD patterns, the average MgH 2 particle was reduced from 35.3 nm to 23.6 nm.…”
Section: Mgh 2 Fritsch Milled For 2 Hrmentioning
confidence: 99%
“…The broad peak seen in the lower angle region is attributed to the kapton film used to prevent oxidation of the samples during measurement. The pattern of the Spex milled sample did reveal peak broadening and lower intensity indicating a decrease in particle size and an increase in defects [29]. Using the Scherrer equation to determine particle size from XRD patterns, the average MgH 2 particle was reduced from 35.3 nm to 23.6 nm.…”
Section: Mgh 2 Fritsch Milled For 2 Hrmentioning
confidence: 99%
“…It is well known that the typical N-H vibrations of Li 2 NH and Li 2 Mg(NH) 2 are at 3163 and 3174 cm À1 , respectively. 15,37) As a result, it can be believed that two phases of Li 2 NH and Li 2 Mg(NH) 2 are involved in the solid residues after dehydrogenated at 310 C. According to dehydrogenation measurements and structural analyses, we can give a picture of the chemical process in heating process of the Mg(NH 3 ) 6 Cl 2 -18LiH combined system. As described above, the starting sample of Mg(NH 3 ) 6 Cl 2 -18LiH converts to the mixture of Mg(NH 2 ) 2 -4LiNH 2 -2LiCl-12LiH after 24 h of milling.…”
Section: )mentioning
confidence: 99%
“…1) In contrast to the compressed hydrogen and the liquefaction hydrogen, hydrogen storage in the solid state is the most promising alternative. [2][3][4][5] In the past decades, the complex hydrides consisting of light elements, e.g., alanates, [6][7][8][9][10] amides, [11][12][13][14][15] borohydrides [16][17][18][19][20] and ammonia borane (AB), [21][22][23] have been attracting extensive attention as the potential hydrogen storage materials due to their high gravimetric and volumetric hydrogen storage densities. In particular, significant efforts have been made in recent years with metal amide-hydride combined systems since Chen et al reported that lithium nitride, Li 3 N could absorb/desorb reversibly 11.4 mass% of hydrogen in 2002.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations